ACAA2 Protects Against Cardiac Dysfunction and Lipid Peroxidation in Renal Insufficiency with the Treatment of S-Nitroso-L-Cysteine - Zhengqi Xu; Feng Jiang; Xiaofan Wu; Bowen Ren; Cuntai Zhang; Li Lin; Sheng Li (Biomolecules)
The key fatty acid β-oxidation protein acetyl-CoA acyltransferase 2 (ACAA2) plays a significant role in myocardial lipid peroxidation and cardiac dysfunction induced by renal insufficiency. However, the mechanisms of lipid metabolism related to renal insufficiency-associated cardiac dysfunction remain poorly understood, and current clinical treatments have been largely ineffective. Through analysis of the Gene Expression Omnibus (GEO) database, we identified that the cardiac functional changes caused by renal insufficiency were primarily centered around the fatty acid β-oxidation signaling pathway, where ACAA2 plays a pivotal role in fatty acid β-oxidation, the tricarboxylic acid cycle, and ketone body metabolism. In an adenine-induced renal insufficiency mouse model, further examination with hematoxylin-eosin staining, Masson staining, and Oil Red O staining revealed alterations in the heart and kidney as well as the accumulation of lipid. Non-invasive blood pressure measurements and ultrasound images demonstrated improvements of peripheral vascular and right ventricular hemodynamic parameters with S-nitroso-L-cysteine (CSNO) inhalation therapy. In cell experiments, knocking down ACAA2 led to accumulation of lipid droplets and exacerbation of oxidative stress in cardiomyocytes, while overexpression of ACAA2 reversed these effects. The transcription factor FOXO4 was found to regulate lipid peroxidation by modulating ACAA2, and knocking down FOXO4 partially restored the expression of ACAA2, reducing oxidative stress in cardiomyocytes. Furthermore, exogenous CSNO effectively restored the expression of ACAA2 and reduced the level of FOXO4, thereby mitigating lipid peroxidation and improving cardiac function. Therefore, in the context of renal insufficiency, regulating the FOXO4–ACAA2 axis through CSNO inhalation therapy may provide a novel therapeutic strategy for alleviating myocardial lipid peroxidation and improving cardiac function.